Multi-omics analysis explores the impact of ofloxacin pressure on the metabolic state in Escherichia coli - Xiaoyu Yi; Miao Feng; Feng He; Zonghui Xiao; Yichuan Wang; Shuowen Wang; Hailan Yao (Journal of Global Antimicrobial Resistance, 2024)
Objectives: The rising threat of antibiotic resistance poses a significant challenge to public health. The research on the new direction of resistance mechanisms is crucial for overcoming this hurdle. This study examines metabolic changes by comparing sensitive and experimentally induced ofloxacin-resistant Escherichia coli (E. coli) strains using multi-omics analyses, aiming to provide novel insights into bacterial resistance. Methods: An ofloxacin-resistant E. coli strain was selected by being exposed to high concentration of ofloxacin. Comparative analyses involving transcriptomics, proteomics, and acetylomics were conducted between the wild-type and the ofloxacin-resistant (Re-OFL) strains. Enrichment pathways of differentially expressed genes, proteins and acetylated proteins between the two strains were analysed using gene ontology and Kyoto Encyclopedia of Genes and Genomes method. In addition, the metabolic network of E. coli was mapped using integrated multi-omics analysis strategies. Results: We identified significant differences in 2775 mRNAs, 1062 proteins, and 1015 acetylated proteins between wild-type and Re-OFL strains. Integrated omics analyses revealed that the common alterations enriched in metabolic processes, particularly the glycolytic pathway. Further analyses demonstrated that 14 metabolic enzymes exhibited upregulated acetylation levels and downregulated transcription and protein levels. Moreover, seven of these metabolic enzymes (fba, tpi, gapA, pykA, sdhA, fumA, and mdh) were components related to the glycolytic pathway. Conclusions: The changes of metabolic enzymes induced by antibiotics seem to be a key factor for E. coli to adapt to the pressure of antibiotics, which shed new light on understanding the adaptation mechanism when responding to ofloxacin pressure.